WASIAT WAJIBAH DALAM PERSPEKTIF HUKUM ISLAM DI INDONESIA DAN KOMPARASINYA DI NEGARA-NEGARA MUSLIM - Erniwati Erniwati (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2018)
One of the laws that is classified as contemporary in the Islamic world is with respect to mandatory wills. Namely the will which the implementation is not influenced or not depends on the willingness or will of the deceased. Testament in this form applies automatically, whether spoken or not spoken, whether desired or not desired by the person who died during his lifetime. The method applied in this writing is a comparative method, namely by comparing the laws and provisions of mandatory wills applied in Indonesia with those prevailing in other Muslim countries. The result is a difference in the application of mandatory testament objects. In Indonesia a compulsory testament applies between foster parents and adopted children or vice versa. Whereas in other Muslim countries, this applies between grandfather and cuccus whose parents have died first